Diagnosis and Treatment of Neuroblastoma Using 131 l-Meta-lodobenzylguanidine - Edeling, C.-J.; Frederiksen, P. Büchler; Kamper, J.; Jeppesen, P. (Nuklearmedizin - NuclearMedicine, 1986)
Neuroblastoma is a lethal and not uncommon tumor in childhood. Early detection and display of the spread of the tumor is highly desirable for proper treatment. Nine children suspected of having neuroblastoma were examined by 131l-meta-iodobenzylguanidine (131I-MIBG) scintigraphy. In two recent studies 123l-meta-iodobenzylguanidine (123I-MIBG) was used. A primary adrenal neuroblastoma was correctly identified in 3 cases. In 2 patients additional tumor sites were found. In one patient, who was in complete remission, no pathological accumulation of 131I-MIBG was found. 131I-MIBG scintigraphies were also normal in 4 patients with other types of tumor. In one girl with a large adrenal neuroblastoma high uptake of 131I-MIBG was observed. She received two therapy doses of 131I-MIBG (1300–2800 MBq) with curative intention giving a total absorbed dose in the tumor of approximately 90 Gy. In spite of high retention of radioactivity in the tumor, regression did not appear, but her general condition was improved. In the present study images of superior quality were obtained by 123I-MIBG scintigraphy. It is concluded that scintigraphy with 131I- or 123I-MIBG should be used for primary visualization and control of neuroblastomas.Das Neuroblastom ist ein letaler und nicht ungewöhnlicher Tumor in der Kindheit. Ein früher Nachweis und eine Sichtbarmachung der Ausbreitung des Tumors ist für eine richtige Behandlung im höchsten Maße wünschenswert. 9 Kinder mit Verdacht auf Neuroblastom wurden mit der 131J-Meta-Jodbenzylguanidin (131JMIBG)- Szintigraphie untersucht. In zwei neueren Studien wurde 123J-Meta- Jodbenzylguanidin (123J-MIBG) benutzt. Ein primäres adrenales Neuroblastom wurde korrekt in drei Fällen identifiziert. Bei zwei Patienten wurden zusätzliche Tumorausbreitungen gefunden. Bei einem Patient, der in kompletter Remission war, fand sich keine pathologische Anreicherung von 131J-MIBG. Die 131J-MIBG-Szintigraphie war außerdem normal in 4 Patienten mit anderen Tumortypen. Bei einem Mädchen mit einem großen adrenalen Neuroblastom wurde eine hohe Anreicherung von 131J-MIBG beobachtet. Sie erhielt zwei Therapiedosen von 131J-MIBG (1300 und 2800 MBq) mit kurativer Absicht, wobei eine totale absorbierte Dosis im Tumor von ungefähr 90 Gy verabreicht wurde. Trotz der hohen Radioaktivitätsanreicherung im Tumor erschien keine Regression, das Allgemeinbefinden wurde jedoch verbessert. In der vorliegenden Studie wurden Bilder von überragender Qualität mit der 123J-MIBG-Szintigraphie erhalten. Es wird die Schlußfolgerung gezogen, daß die Szintigraphie mit 131J- oder 123 J-MIBG für die Primärdarstellung und Kontrolle des Neuroblastoms eingesetzt werden sollte.